The development of the performance sex gap in track-and-field events across the lifespan - Balcarova, B.; Pedersen, A. (Frontiers in Sports and Active Living, 2025)
Due to sexual dimorphism, men outperform women in athletics, and thus they compete separately. Although the difference, called "the performance sex gap", was thought to be stable across the lifespan, our research suggests that the gap changes with age. In our study, using publicly accessible databases, we collected data about top performances by men and women 5 to 100 years old in 18 track-and-field events sorted into three categories: running, jumping, and throwing. Our results suggest that the magnitude of the performance sex gap changes across the lifespan; it emerges in prepubertal children, widens among adolescents, stabilizes among senior athletes (i.e., 20-34 years old), and further increases among masters athletes (i.e., 35+ years old). Among seniors, the gap has been narrower in running events (i.e., approx. 10%) than in jumping events (i.e., approx. 15%). In throwing events, the gap differs considerably, largely due to the variable scaling of throwing implements based on sex and age group. Among masters, for instance, those implements are generally scaled down more for men than for women, which makes sex-based comparisons difficult. Beyond that, scaling in general is vaguely defined and varies across countries and events for children athletes (i.e., 5-15 years old). Altogether, our results indicate that not only physiology but also event-specific tasks and environmental constraints influence the performance sex gap. To ensure fair scaling, throwing implements used among masters women athletes may need to be downscaled to allow an appropriate comparison of how performance develops in both sexes.